Direct Room-Temperature Synthesis of Organic-Inorganic Hybrid MCM-48 Nanoparticles - Luo, Xu; Wang, Zhonglai; Zou, Guojun; Wang, Xiaolai (Asian Journal of Chemistry, 2013)
A series of organic-inorganic hybrid MCM-48 materials were directly synthesized by a rapid and facile way at room temperature without employing hydrothermal synthesis for the first time. The resultant samples were characterized through XRD, N2 adsorption/desorption, FT-IR, FESEM and HRTEM. The characterization results revealed that all the samples with typical mesoporous structure were successfully modified by the introduced organic groups.